IMPROVING SPEAKING SKILLS THROUGH BARA LEARNING APPROACH IN EFL CLASSROOM - Widiastuti, Ida Ayu Made Sri; Mantra, Ida Bagus Nyoman (Jurnal Cakrawala Ilmiah, 2024)
Speaking abilities are crucial language skills that must be consistently and thoroughly developed to increase a student's language proficiency. This study used a classroom action research design involving two cycles of learning activities; the BARA learning approach was carried out to improve students' speaking abilities. The four learning phases of the BARA approach, consisting of brainstorming, activating, reinforcing, and applying, were developed by Indonesian educators. The final BARA learning method design was created through this BARA approach trial in an EFL classroom. Data was gathered using a questionnaire, pretests, and posttests. The student's speaking skills significantly improved in the first and second learning cycles compared to the pretest result. Consequently, the BARA approach successfully improves students' English speaking skills